Intrahepatic cholestasis of pregnancy- case series done in a tertiary care hospital - Kaundinya, Aditi; Pawde, Anuya; Sudharani, G.; Gopal, Sriram; More, Mayuri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Intrahepatic cholestasis of pregnancy (ICP) also known as obstetric cholestasis is a liver disorder of pregnancy which is characterised by maternal pruritus usually in the third trimester, raised serum bile acids and increased incidence of adverse fetal outcomes and usually complete resolution of symptoms post-delivery. The etiology of ICP is complex and multifactorial as is the mechanism by which fetal complications occur which is yet not completely understood. The introduction of ursodeoxycholic acid in the management of ICP has provided significant improvement in maternal symptoms as well as fetal outcome. We present a case series of 5 cases of obstetric cholestasis which presented in our tertiary care hospital which could possibly help and guide obstetricians in the future who are dealing with dilemma in diagnosis and management of this condition.